Association Between Antimicrobial Resistance and the Clinical Evolution of Patients with Infections in the Pediatric Intensive Care Unit of the National Institute of Pediatrics - Scott Macías; Alejandra Aquino; Agustín R de Colsa; Jocelin Merida; Virginia Diaz; Damaris Manzano; Isabel Medina (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background Sepsis is the most common cause of the over two million annual deaths from worldwide infections. The World Health Organization is focused on optimizing early diagnosis, treatment, and prevention. The rise of multidrug-resistant (MDR) bacteria limits conventional antibiotics. Healthcare-associated infections (HAIs) are frequent in pediatric and neonatal intensive care units, leading to higher mortality and costs. Essential strategies include strengthening surveillance, infection control, and developing new antimicrobials. This study analyzes the demographics, risk factors, and clinical outcomes of sepsis in PICU patients to propose evidence-based interventions. Methods Patients were identified through clinically significant cultures of selected bacterial pathogens. Clinical variables, treatment, and outcomes were recorded, with follow-up extending beyond PICU discharge. Susceptibility profiles were classified using Clinical Laboratory Standards Institute (CLSI) criteria, and treatment adequacy was evaluated. All eligible cases were included without sampling. Results A total of 97 clinically significant isolates were included, predominantly Gram-negative bacilli—mainly Enterobacterales (63%) and non-fermenters (23.7%). The most common pathogens were Klebsiella pneumoniae, Escherichia coli, and Pseudomonas aeruginosa. Enterobacterales showed >50% resistance to beta-lactams and carbapenems, driven mainly by ESBLs and NDM carbapenemases. Adolescents had higher mortality, and central-line-associated bloodstream infections were associated with worse outcomes. Overall 30-day mortality was 20.6%, with one-third infection-attributable. Hospital-acquired infections and invasive devices significantly increased the risk of death. Pseudomonas spp. showed 58% carbapenem resistance, while Acinetobacter spp. had 30% resistance to piperacillin/tazobactam and carbapenems. Most patients received empirical therapy, and combination regimens were linked to better survival. These findings highlight the high burden and limited treatment options for MDR Gram-negative infections in the PICU. Conclusion MDR Gram-negative infections remain a critical cause of sepsis and mortality in the PICU. The predominance of NDM carbapenemases highlights the urgent need to reinforce infection-control policies, optimize antimicrobial stewardship, and incorporate new antibiotic options targeting these resistance mechanisms into pediatric treatment protocols to improve clinical outcomes and reduce mortality.